Canthaxanthin biosynthesis by Dietzia natronolimnaea HS-1: effects of inoculation and aeration rate - Rostami, Forouzan (Sociedade Brasileira de Microbiologia, 2014)
The interest in production of natural colorants by microbial fermentation has been currently increased. The effects of D-glucose concentration (3.18–36.82 g/L), inoculum size (12.5 × 10(9)–49.5 × 10(9) cfu cells/mL) and air-flow rate (1.95–12.05 L/L min) on the biomass, total carotenoid and canthaxanthin (CTX) accumulation of Dietzia natronolimnaea HS-1 in a batch bioreactor was scrutinized using a response surface methodology-central composite rotatable design (RSM-CCRD). Second-order polynomial models with high R(2) values ranging from 0.978 to 0.990 were developed for the studied responses using multiple linear regression analysis. The models showed the maximum cumulative amounts of biomass (7.85 g/L), total carotenoid (5.48 mg/L) and CTX (4.99 mg/L) could be achieved at 23.38 g/L of D-glucose, 31.2 × 10(9) cfu cells/mL of inoculation intensity and air-flow rate of 7.85 L/L min. The predicted values for optimum conditions were in good agreement with experimental data.